Value of endometrial biopsy in the diagnosis of ectopic pregnancy - Gutiérrez Manay, Juan (2015)
Atypical endometrial disorder associated with the presence of chorionic tissue in 50% of 44 cases of ectopic pregnancy is. At 36.36 (16 cases) is decidual reaction. Based on the classic concept that ectopic pregnancy can be diagnosed only by the presence of decidual reaction and the new concept of atypia related to the presence of chorionic tissue, this suggestion had been made at 63.63%. The glandular atypia, is therefore, a new addition to the diagnosis of ectopic pregnancy, to accrue the value of biopsy and gynecological auxiliary means. It draws attention to the importance and significance of changes in minor or minimal degree and atypical occurrence in the lining epithelium (40.9%). It described for the first time the occurrence of glandular atypia in a case of internal endometriosis associated with ectopic pregnancy. We propose the name of Injury Arias-Stella atypical endometrial glandular disorders, for being this Peruvian student, who first pointed out in the endometrium in relation chorionic tissue. The occurrence of hyaline aspect fibrinoid necrosis in the stroma of two cases described. There is no relationship between the glandular atypia and local inflammatory processes. No alterations atypical tubal epithelium similar to the endometrium. A correlation between the presence of atypia in the endometrium and the state of vitality of the chorionic villi is shown.